Comparative analysis of iPSC-derived NK cells from two differentiation strategies reveals distinct signatures and cytotoxic activities - Huyghe, Matthias; Desterke, Christophe; Imeri, Jusuf; Belliard, Nathan; Chaker, Diana; Oudrirhi, Noufissa; Bezerra, Hudson; Turhan, Ali G.; Bennaceur-Griscelli, Annelise; Griscelli, Frank (Frontiers in Immunology, 2024)
The ability to generate natural killer (NK) cells from induced pluripotent stem cells (iPSCs) has given rise to new possibilities for the large-scale production of homogeneous immunotherapeutic cellular products and opened new avenues towards the creation of "off-the-shelf" cancer immunotherapies.However, the differentiation of NK cells from iPSCs remains poorly understood, particularly regarding the ontogenic landscape of iPSC-derived NK (iNK) cells produced in vitro and the influence that the differentiation strategy employed may have on the iNK profile. To investigate this question, we conducted a comparative analysis of two sets of iNK cells generated from the same iPSC line using two different protocols: (i) a short-term, clinically compatible feeder-free protocol corresponding to primitive hematopoiesis, and (ii) a lymphoid-based protocol representing the definitive hematopoietic step. Our work demonstrated that both protocols are capable of producing functional iNK cells.However, the two sets of resulting iNKs exhibited distinct phenotypes and transcriptomic profiles. The lymphoid-based differentiation approach generated iNKs with a more mature and activated profile, which demonstrated higher cytotoxicity against cancer cell lines compared to iNK cells produced under short-term feeder-free conditions suggesting that the differentiation strategy must be considered when designing iNK cell-based adoptive immunotherapies.